THE THE CHATOLIC TEACHERS’S ROLE IN ACCUSTOMING THE STUDENTS TO DO PRACTICAL PASTORAL IN SINGKAWANG - Ona Sastri Lumban Tobing; Exnasia Retno Palupi Handayani; Florentina Dwi Astuti (Jurnal Scientia, 2023)
Practical Pastoralism is a fundamental thing that can shape oneself and the source of ministry. Through practical pastoral care, you can train yourself and deepen spirituality, which is a believer's relationship with God through individual and group life practices through various manifestations in attitudes and actions. Distinctive or unique practical pastoralism is always associated with a person's experience of cultural and religious values and beliefs, as well as certain social, economic, political and ideological values and beliefs which are always associated with their calling in life and the values they adhere to. The spirit that underlies the pattern of life and behavior as well as the way of working is greatly influenced by the calling in life through which they find the special meaning and meaning of their lives. Catholic schools, as educational institutions that are inseparable from the influence of the Church, form students in the formation of a spiritual life through practical pastoral care and getting used to being involved in the life of the church and society. The role of PAK teachers is to transfer knowledge and faith values to their students. These teachers must be role models for each individual student. An example is a characteristic for every individual who is able to make decisions and is responsible for the way they think and behave regarding the decisions they make. Practical pastoral forms that familiarize students so that they are involved in church and community life in everyday life as a form of actualization as well as basic training in instilling the values of Faith that live in the midst of the Church and society